A Kinetic Study On Cellulase Enzymes From Aspergillus Niger - SAXENA ARTI; SAXENA ANURAG; YADAV SARIKA (International Journal of Pharma and Bio Sciences, 2011)
A physico-chemical study was made on cellulase enzymes from a highly cellulolytic fungus Aspergillus niger. Various kinetic parameters were estimated by making use of potent fungicides, viz. m-dinitrobenzene and pentachlorophenol. The enzyme showed maximum activity at pH 5.0 and temp. 55o C. The half-life was found to be 42 minutes at optimum pH. The Michaelis Constant, Km, was observed as 13.3mM and Vmax. as 6.65µM/sec. The inhibition constant, Ki, for MDB was observed to be 19.2mM and for PCP as 22.6mM, thereby indicating that MDB is a more potent inhibitor than PCP.